Evaluation of composted coir p ith with chemical and biofertilizers on nutrient availability, yield and quality of b lack pepper (Piper nigrum L.) - Sadanandan, V Srinivasan, S Hamza, A K (Journal of Spices and Aromatic Crops, 2005)
Composted coir pith was evaluated at Madikeri (Karnataka) under integrated plant nutrient management system to substitute chemical input of fertilizers for improving the yield and quality of black pepper (Piper nigrum). Application of composted coir pith (CC) @ 2.5 t ha" with full recommended dose of NPK (100:40:140 kg ha" of N, P,O, and K, O) yielded the highest (4.18 kg vine" ) which was on par with 1.25 t ha·1 CC + full NPK, 2.5 t ha·1 CC + y, NPK + Azospirillum sp., 1.25 t ha" CC + y, NPK + Azospirillum sp. and 2.5 t ha" CC alone. The levels of composted coir pith application were on par with regard to quality (piperine and oleoresin contents). of black pepper. The highest benefit-cost ratio of 1.94 was recorded in the ,treatment with composted coir pith @ 1.25 t ha" + Azospirillum sp.